HANS KELSEN'S PURE THEORY OF LAW AS A THEORETICAL PILLAR IN THE DYNAMICS OF THE MODERN LEGAL SYSTEM IN INDONESIA - ISKANDAR, M.; TRADESA, ANGGI PURNAMA; TITI TANTRI (LOIS: Jurnal Hukum dan Humaniora, 2025)
This research was conducted with the aim of determining how Hans Kelsen's Pure Legal Theory fits into the Modern Legal Paradigm Based on Humanity and Social Justice. This research is a normative legal research. Normative legal research is often referred to as doctrinal legal research. The legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. The existing legal materials were collected through literature studies, which were then normatively analyzed to answer the problems studied. The results of this research are that the application of Hans Kelsen's Pure Legal Theory in Indonesian law shows a process of adaptation and contextualization. Kelsen's stufenbau theory concept is relevant in explaining the hierarchy of laws and regulations. However, in terms of basic norms, Indonesia does not adhere to a neutral grundnorm, but rather places Pancasila as the source of all sources of law. In addition, customary law also plays an important role as part of Indonesia's legal pluralism, which is recognized by the constitution.